Modified oxylipins as inhibitors of biofilm formation in Staphylococcus epidermidis - Peran, Jacquelyn E.; Salvador-Reyes, Lilibeth A. (Frontiers in Pharmacology, 2024)
New approaches to combating microbial drug resistance are being sought, with the discovery of biofilm inhibitors considered as alternative arsenal for treating infections. Natural products have been at the forefront of antimicrobial discovery and serve as inspiration for the design of new antibiotics. We probed the potency, selectivity, and mechanism of anti-biofilm activity of modified oxylipins inspired by the antibiofilm marine natural product turneroic acid. Structure-activity relationship (SAR) evaluation revealed the importance of the trans-epoxide moiety, regardless of the position, for inhibiting biofilm formation. trans-12,13-epoxyoctadecanoic acid (1) and trans-9,10 epoxyoctadecanoic acid (4) selectively target the early stage of biofilm formation, with no effect on planktonic cells. These compounds interrupt the formation of a protective polysaccharide barrier by significantly upregulating the ica operon's transcriptional repressor. This was corroborated by docking experiment with SarA and scanning electron micrographs showing reduced biofilm aggregates and the absence of thread-like structures of extrapolymeric substances. In silico evaluation revealed that 1 and 4 can interfere with the AgrA-mediated communication language in Staphylococci, typical to the diffusible signal factor (DSF) capacity of lipophilic chains.